Role of p73 Dinucleotide Polymorphism in Prostate Cancer and p73 Protein Isoform Balance - L. Michael Carastro; Hui-Yi Lin; Hyun Y. Park; Donghwa Kim; Selina Radlein; Kaia K. Hampton; Ardeshir Hakam; Babu Zachariah; Julio Pow-Sang; Jong Y. Park (Prostate Cancer)
Background. Molecular markers for prostate cancer (PCa) risks are currently lacking. Here we address the potential association of a dinucleotide polymorphism (DNP) in exon 2 of the p73 gene with PCa risk/progression and discern any disruption of p73 protein isoforms levels in cells harboring a p73 DNP allele. Methods. We investigated the association between p73 DNP genotype and PCa risk/aggressiveness and survival by fitting logistic regression models in 1,292 incident cases and 682 controls. Results. Although we detected no association between p73 DNP and PCa risk, a significant inverse relationship between p73 DNP and PCa aggressiveness (AT/AT + GC/AT versus GC/GC, OR = 0.55, 95%Cl = 0.31–0.99) was detected. Also, p73 DNP is marginally associated with overall death (dominant model, HR = 0.76, 95%Cl = 0.57–1.00, P=0.053) as well as PCa specific death (HR = 0.69, 95%Cl = 0.45–1.06, P=0.09). Western blot analyses for p73 protein isoforms indicate that cells heterozygous for the p73 DNP have lower levels of ∆Np73 relative to TAp73 (P<0.001). Conclusions. Our findings are consistent with an association between p73 DNP and low risk for PCa aggressiveness by increasing the expressed TAp73/∆Np73 protein isoform ratio.